2020
DOI: 10.4317/jced.57599
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of microhardness, sorption, solubility, and color stability of bulk fill resins: A comparative study

Abstract: Background Due to the increasing popularity of bulk fill resins, there is a concern that their components can be leached; this is because these are inserted in a single 4-5 mm increment. This in vitro study evaluated the microhardness, sorption, solubility, and color stability of three restorative bulk fill resins, namely: Filtek Bulk Fill (FBF), Tetric N-Ceram Bulk Fill (TNC), and Opus Bulk Fill (OBF). Material and Methods Cylindrical samples were fabricated to be 15 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…This could contribute to improving the survival rate of restorations since it has been reported that having poor surface properties can lead to pigment retention, plaque, the possibility of fracture, and secondary caries formation [ 9 , 10 , 11 , 30 ]. As a strength of the present study, it should be mentioned that several authors such as Wheeler et al [ 12 ], Paravina et al [ 21 ], Espindola et al [ 51 ], and Bouschlicher et al [ 53 ] have assessed only one surface property of resin composites, while in the present study, two surface properties could be assessed in the same sample unit, reducing the bias that would be obtained by assessing surface microhardness and surface roughness in different study units. Furthermore, according to the obtained results, it is evident that the Tetric N-Ceram Bulk Fill and Filtek Bulk Fill resin composites with OIL control and after polishing improved their surface properties, which could favor a better esthetic and functional performance under masticatory forces [ 25 , 39 , 40 , 46 ], while in the case of Opus Bulk Fill, only its surface roughness was significantly improved, which could allow a better esthetic performance but not necessarily an improvement in its resistance to masticatory forces.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…This could contribute to improving the survival rate of restorations since it has been reported that having poor surface properties can lead to pigment retention, plaque, the possibility of fracture, and secondary caries formation [ 9 , 10 , 11 , 30 ]. As a strength of the present study, it should be mentioned that several authors such as Wheeler et al [ 12 ], Paravina et al [ 21 ], Espindola et al [ 51 ], and Bouschlicher et al [ 53 ] have assessed only one surface property of resin composites, while in the present study, two surface properties could be assessed in the same sample unit, reducing the bias that would be obtained by assessing surface microhardness and surface roughness in different study units. Furthermore, according to the obtained results, it is evident that the Tetric N-Ceram Bulk Fill and Filtek Bulk Fill resin composites with OIL control and after polishing improved their surface properties, which could favor a better esthetic and functional performance under masticatory forces [ 25 , 39 , 40 , 46 ], while in the case of Opus Bulk Fill, only its surface roughness was significantly improved, which could allow a better esthetic performance but not necessarily an improvement in its resistance to masticatory forces.…”
Section: Discussionmentioning
confidence: 77%
“…Previous studies have shown that ivocerin acts as a polymerization enhancer, allowing it to be efficient [ 2 , 3 , 49 ]. Filtek Bulk Fill is a composite resin that has camphorquinone as a photoinitiator, with an absorption peak of approximately 470 nm that matches the wavelength emitted by most LED-curing lights on the market [ 51 ], which could improve the conversion degree of the resin composite by increasing its surface microhardness, as it has been shown with a variety of different composite resins that 80% of maximum hardness is associated with 90% of maximum polymerization [ 52 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Any disagreement was resolved by discussion. After full text reading 178 studies 11,13–189 were included in the review (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…9 These alterations promote a change in surface smoothness, loss of gloss, and color change because the surface roughness also interferes directly with the intensity and rate of pigmentation. 13 - 14 This is why it is imperative to assess the characteristics of these toothpastes and their effect on restorative materials.…”
Section: Introductionmentioning
confidence: 99%
“… 5 , 13 Intrinsic factors are associated with material degradation due to components such as organic matrix composition and the initiator system, whereas the size, content, and hardness of the filler particles are directly influenced by photopolymerization. 14 - 15 Extrinsic factors are associated with pigment adsorption and absorption derived from sources such as nicotine, medications, and the patient’s diet. 14 - 15 Color stability can be compromised by chromogenic beverages, depending on the pH, and the frequency and duration of contact of these beverages with the material.…”
Section: Introductionmentioning
confidence: 99%